Social Proof As A Moderating Variable on The Influence of Brand Awareness on Purchasing Decisions - Efti Novita Sari; Liestyowati Liestyowati; Akhmad Julian Saputra; Aryadi Aryadi; Hamdiah Hamdiah (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze and test the role of social proof as a moderating variable in the relationship between brand awareness and purchasing decisions. In the highly dynamic digital economy era, consumers are faced with abundant product information, so brand recognition alone is no longer sufficient to guarantee a purchasing decision. A quantitative approach was used in this study with an explanatory design. The research sample included active e-commerce consumers selected through a purposive sampling technique. Data collection was conducted using a structured questionnaire with a 5-point Likert scale, and data analysis was tested using Structural Equation Modeling - Partial Least Squares (SEM-PLS) through SmartPLS software. The results of the analysis indicate that brand awareness has a positive and significant effect on purchasing decisions. Furthermore, moderation testing confirmed that social proof significantly strengthens the influence of brand awareness on purchasing decisions. These findings indicate that when consumers have high brand awareness and are reinforced by social validation such as positive reviews, product ratings, and influencer recommendations the probability of a purchasing decision will increase exponentially. The theoretical implications of this study expand the framework of Signaling Theory and Social Influence Theory in the context of modern consumer behavior, while its practical implications provide strategic guidance for marketing practitioners to integrate influencer marketing and user-generated content strategies to optimize sales conversions. Keywords: Brand Awareness, Purchasing Decisions, Social Proof, Moderating Variables, SEM-PLS.